Factors influencing the salt requirements of beef cattle. The effect of withholding salt on the growth and condition of steers. - Smith, E.F.; Parrish, D.B.; Splitter, E.J. (Kansas Agricultural Experiment Station, 2012)
The object of this test was to learn what effect withholding salt, has on fattening calves. Twenty good quality Hereford steer calves were divided into two lots of 10 steers each and were self-fed a mixture of 1 pound of chopped alfalfa hay to 3 pounds of ground milo grain for 203 days in 1951-52. The only difference in treatment was that salt was withheld from one lot and offered free choice in the other lot.
Keywords: Beef; Salt; Growth; Condition